SAT0197 Ultrasound Guided Musculoskeletal Procedures under Peripheral Nerve Block: A Pilot Controlled Study in Rheumatic Patients. (10th June 2014) - Coutinho, M.; Duarte, C.; Ferreira, J.; Da Silva, J.
Abstract : Background: Musculoskeletal Ultrasound (US) is a valuable tool in the diagnosis and monitoring of rheumatic diseases. Invasive musculoskeletal procedures under US guidance improve technical accuracy and efficacy. However, patients complain of considerable pain during these procedures, which may compromise patient cooperation and technical efficacy. Peripheral nerve blocks (PNBs) allow an effective local anaesthesia, without significant adverse effects. Objectives: To investigate the feasibility of PNBs in patients undergoing US-guided invasive procedures and their impact upon the pain induced by the procedure and its efficacy. Methods: Consecutive patients requiring US-guided invasive procedures were recruited. Patients were randomly allocated, in blocks of 5, to two treatment groups. Group 1 had a local peripheral nerve block using 5ml of lidocaíne cloridrate 2% and Group 2 had a topical anaesthetic applied before the US-guided procedure. Demographic and clinical parameters and current therapies were registered. US examination of the anatomical region of pain was performed and effusion, synovial hypertrophy, hipoechoic tendon halus and Power Doppler (PD) signal were evaluated (synovitis, defined as the presence of effusion and/or synovial hypertrophy, was scored in gray-scale from mild to severe;PD signal was scored in a 0-3 scale). US evaluation and pain assessment were performed at baseline and 2 weeks after the US-guided procedure. Patients were asked to score the pain spontaneously felt at the region of interest over the previous week, using a Visual Analog Scale (VAS;0-100mm). Pain caused by the procedure was evaluated as above, 5 minutes after its performance. Efficacy of the procedure was defined as a reduction ≥1 point in synovitis and/or PD score and as a reduction ≥15mm in patient pain VAS. Comparison between groups was performed through Chi2 or Independent Samples T test, as adequate. p<0.05 was considered significant in statistical analyses. Results: Sixty-one patients were included (Group 1=36;Group 2=25). Rheumatoid arthritis was the most frequent underlying rheumatic disease (34.4%). In Group 1, deep peroneous nerve block and an association of radial and ulnar nerve blocks were the most commonly PNBs executed (52.7% and 38.9%, respectively). No postblock complications were reported. Demographic and clinical parameters and patient pain VAS (previous week) were similar in both groups, although initial US gray-scale findings were significantly higher in Group 1 (p=0.04). The difference in the nature of procedures performed in the two groups was close to statistical significance (p=0.06). Efficacy based on pain responder rates was similar in both groups (66.7% vs 52.6%;p=0.34). Efficacy of the US-guided procedure (at 2 weeks) using responder rates was also similar in both groups (58.3% vs 52.0%;p=0.13). Pain caused by the US-guided procedure was significantly lower in Group 1 (3.36±2.86 vs 5.08±2.41;p=0.017). Conclusions: PNBs were superior to topical anaesthetic in relieving pain due to musculoskeletal US invasive procedures. PNBs are simple and fully acceptable by patients. The differences in the degree of baseline US inflammation and in the nature of the procedures performed in each group, together with the small sample size, preclude final conclusions regarding potential differences in efficacy of the procedures performed under nerve blocks vs local anaesthetic. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5575